Effectiveness of Oil-Based Facial Cleansers (Oil Cleansing) for Acne-Prone Skin : A Systematic Review - Auliani Deby Veronica; Deriel Elka Hidayat (The Indonesian Journal of General Medicine, 2026)
Introduction: Oil cleansing is a popular skincare practice for acne-prone skin, yet the clinical efficacy of oil-based formulations remains unclear due to heterogeneous evidence. This systematic review evaluates the effectiveness of topical oil-containing products on acne outcomes. Methods: A systematic search was performed following PRISMA guidelines. Human clinical studies evaluating oil or essential oil-containing topical formulations for acne vulgaris with at least 2 weeks duration were included. Primary outcomes were lesion count reduction, acne severity scores, and inflammatory markers. Results: The double-blind RCT by Infante et al. (2023) demonstrated that tea tree oil nanoemulsion significantly reduced comedone count (p<0.001) and improved follicular hyperkeratinization. Da Silva et al. (2012) reported copaiba essential oil gel significantly decreased acne-affected surface area (r²=0.695, p=0.000). Mazzarello et al. (2020) showed myrtus and origanum essential oils combined with tretinoin reduced erythema superior to clindamycin-tretinoin (p=0.0329). Meier et al. (2012) found jojoba oil clay mask achieved 54% total lesion reduction (p<0.05 for all lesion types). Kim et al. (2018) reported myrtle essential oil regimen reduced acne grade from 1.8 to 0.9 (p=0.001). Nong et al. (2023) demonstrated bakuchiol-containing regimen reduced total facial lesions by 25.2% (p<0.05). Secondary outcomes included significant sebum reduction and improved hydration. Safety was favorable with minimal irritation. Discussion: The most robust evidence supports tea tree oil nanoemulsion, copaiba oil, and myrtle essential oil. Formulation delivery system critically determines efficacy. Study quality varies; placebo-controlled RCTs show significant but modest effects. No evidence exists for pure oil cleansing method. Conclusion: Oil-containing formulations, particularly with tea tree, copaiba, or myrtle oils in optimized vehicles, demonstrate significant efficacy for mild-to-moderate acne. Advanced delivery systems enhance outcomes. Pure oil cleansing lacks evidence.